The Importance and Practice of Phraseological Units in Our Lives - Tajiboyeva Fotimaxon Vohidjon qizi (Zien Journals, 2022)
Phraseology is a branch of linguistics. Phraseology is derived from Latin, prasis means expression, logos means doctrine. • A phrase is a fixed combination of two or more words in a language that has a figurative meaning and is equivalent to one word.
Keywords: linguistics; compound; Western Europe; center